ANALISIS PENENTUAN KOMODITI UNGGULAN SEKTOR PERTANIAN KABUPATEN ACEH BARAT - Liston Siringo ringo; Agustiar Agustiar (Universitas Teuku Umar, 2017)
This study aims to identify agricultural superior commodities and priorities for the development of the commodity each sub-district of West Aceh district. The methods used for reaching these goals are the analysis method Loqation Quatient (LQ) and Shift Share Analysis (SSA). The data used are secondary data. The results showed that the leading commodity first development priority is as follows: food crops sub-sector is the durian, langsium, orange, guava,water quava, banana and jackfruit. Subsector plantation crop is rubber. Livestock sub-sector is domestic poultry, cow and buffalo. Fishery sub-sector is tilapia and catfish.